The effects of pupil dilation on MAIA microperimetry - Jolly, J; Han, R; Xue, K; MacLaren, R (Wiley, 2017)
Background MAIA microperimetry assesses macular sensitivity to projected point light sources and maps eye movements to assess fixation stability. While microperimetry is gaining prominence as an assessment tool in clinical and research settings, there is no consensus on whether it should be performed before or after pupil dilation. No studies to date have examined the effect of pupil dilation on results. The aim of this project was to elucidate the effect of pupil dilation on microperimetry outcomes. Design Prospective audit. Participants Twenty healthy patients from post-operative cataract clinic and ten patients with choroideremia to simulate a disease with peripheral visual field loss. Methods Subjects underwent 10-2 68 point field testing using the MAIA microperimeter on each eye. Subjects then underwentrandomised dilation of one eye and the test was repeated in both eyes. Main Outcome Measure We compared changes in threshold sensitivity and fixation stability pre- and post-pupil dilation. The undilated eye was analysed for any learning or fatigue effect caused by test repetition. Results Dilation produced no significant effect on threshold sensitivity (dilation effect: -0.29 decibels (dB), p=0.23) or fixation stability in healthy controls or in choroideremia patients (dilation effect: +0.08log bivariate contour ellipse area (BCEA) p = 0.14). There was also no significant learning effect seen in the undilated eye, with no improvement in threshold sensitivity (order of eye testing: +0.03logBCEA, p=0.71). Conclusions In the clinical setting patients may be tested for 10 degree microperimetry with or without pupil dilation, as both scenarios yield consistent and interchangeable results.